(3GdMSfI hGdSjFI (B/s - (3GHf JjejI, CMeO Hf YHO GdMdje Hf YHO GdSdGe,s 661-728 (3g`(B.s; (3GdNTJ, eMeO YKeGfs ((3HjQhJ (B:s (3OGQ GdcJGH GdYQHj,s, 1985)
(3jJfGhd GdcJGH JaSjQ hJMdjd bhd Gddg JYGdi (B: (3eG CUGHc ef MSfI aef Gddg heG CUGHc ef SjFI aef faSc, hjMGhd GdEeGe GHf JjejI Cf jcTa GdfbGH Yf HYV eG JVefJg gPg GdBjI GdcQjeI ef GdMce GdYXjeI hGdahGFO GdcKjQI(B. (3hjbhe aj SHjd Pdc HJYQja GdMSfI hJYQja GdSjFI hHjGf GdaQhb GdeJYOOI GdJj HjfgeG hgh jSdc aj gPG GdcJGH eSdcg GdPj YgOfGg efg MjK jYQV ddehVhY aj ehVhYjI cGedI hjOhQ eY GdOdjd hGdMLI MjKeG OGQG eJHYG aj cd NWhI jNWhgG GdcJGH hGdSfI eSJQTOG HeG bGdg GdSda GdUGdM heG fU Ydjg GdYbd GdSdje(B.s
(3CMeO(B.s
Keywords: (3GdhYX hGdEQTGOs; (3GdMSfGJ hGdSjFGJs; (3GdKhGH hGdYbGHs